Supporting Child Development Through Parenting Interventions in Low- to Middle-Income Countries: An Updated Systematic Review - Zhang, Linlin; Ssewanyana, Derrick; Martin, Marie-Claude; Lye, Stephen; Moran, Greg; Abubakar, Amina; Marfo, Kofi; Marangu, Joyce; Proulx, Kerrie; Malti, Tina (Frontiers in Public Health, 2021)
Background: Over 250 million children in low- and middle-income countries are at risk of not achieving their fullest developmental potential due to co-occurring risks such as poor nutrition and inadequate learning opportunities. Early intervention programs integrating the aspects of nurturing care, that is, good health, adequate nutrition, safety and security, responsive caregiving, and learning opportunities, may ameliorate against the negative impact of these adverse conditions. Methods: This meta-analytic review updates the evidence base of parenting interventions comprising stimulation and responsive caregiving components on developmental outcomes for children under age two years in low- and middle-income countries. It also describes and assesses the moderation effects of population characteristics and implementation features on the intervention effectiveness. Studies were identified based on previous systematic reviews and an updated literature search in eight databases and the grey literature up to December 2020. A random-effect model was used to explore the pooled effect sizes accounted for by the intervention for developmental outcome of cognition, language, motor and social-emotional capacities. Exploratory moderation analyses were also conducted. Results: Twenty-one randomized controlled trials representing over 10,400 children from 12 low- and middle-income-countries and regions across three continents (Africa, Latin America, and Asia) were identified. The interventions showed overall small-to-moderate effects on children’s cognitive development (ES = 0.44; 95% CI = [0.30, 0.57]); language development (ES = 0.33; 95% CI = [0.18, 0.49]); and motor skills (ES = 0.21; 95% CI = [0.10, 0.32]). The overall effect on social-emotional development was non-significant (ES = 0.17; 95% CI = [-0.01, 0.34]). Effect sizes (ES) varied significantly across the studies. Parenting programs that targeted vulnerable groups, including rural communities and caregivers with lower education levels, had more significant effects on children’s development. Group sessions (vs. individual visits) and high program dose (≥12 sessions) were associated with stronger effects on child development. Further research is needed to determine the effectiveness of workforce and training on programmatic outcomes. Conclusion: The findings indicate that parenting interventions that encourage nurturing care are effective in improving the early development of children, especially among vulnerable populations. We discuss opportunities to strengthen the implementation of research-based parenting interventions.